2010
DOI: 10.1186/1423-0127-17-90
|View full text |Cite
|
Sign up to set email alerts
|

Direct electrochemical analyses of human cytochromes b5 with a mutated heme pocket showed a good correlation between their midpoint and half wave potentials

Abstract: BackgroundCytochrome b5 performs central roles in various biological electron transfer reactions, where difference in the redox potential of two reactant proteins provides the driving force. Redox potentials of cytochromes b5 span a very wide range of ~400 mV, in which surface charge and hydrophobicity around the heme moiety are proposed to have crucial roles based on previous site-directed mutagenesis analyses.MethodsEffects of mutations at conserved hydrophobic amino acid residues consisting of the heme pock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
1
10
1
Order By: Relevance
“…We demonstrated that the reaction cycle of BaP oxidation catalyzed by human P450 1A1 can proceed by ways that differ from the generally accepted mechanism, where the first reduction of P450 is considered to be catalyzed by POR without cytochrome b 5 . 20 , 48 52 Considering the redox potentials of cytochrome b 5 (+20 mV) 53 , 54 and ferric substrate-bound P450 (−237 mV), 27 , 53 it is thermodynamically impossible for cytochrome b 5 to provide the first electron in the P450 catalytic cycle. 55 Given that the redox potential of oxyferrous P450 is also approximately +20 mV, it is feasible that cytochrome b 5 can supply the second electron into the catalytic cycle.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the reaction cycle of BaP oxidation catalyzed by human P450 1A1 can proceed by ways that differ from the generally accepted mechanism, where the first reduction of P450 is considered to be catalyzed by POR without cytochrome b 5 . 20 , 48 52 Considering the redox potentials of cytochrome b 5 (+20 mV) 53 , 54 and ferric substrate-bound P450 (−237 mV), 27 , 53 it is thermodynamically impossible for cytochrome b 5 to provide the first electron in the P450 catalytic cycle. 55 Given that the redox potential of oxyferrous P450 is also approximately +20 mV, it is feasible that cytochrome b 5 can supply the second electron into the catalytic cycle.…”
Section: Discussionmentioning
confidence: 99%
“…This value is ca. 0.1 V higher compared to the redox potential of b5-type cytochromes (Aono et al, 2010;Rivera et al, 1998), but it is in good agreement with the redox potential of hSOx (Johnson-Winters et al, 2010;Sezer et al, 2010). From the non-turnover reduction peak current (I p ) at a given scan rate v the surface coverage Γ of electrochemically active hSOx was calculated using Γ = I RT v F A 4 / n p 2 2 , where n is the number of electrons transferred, R the gas constant, T the temperature and F is the Faraday constant.…”
Section: Electrode Characterisationmentioning
confidence: 95%
“…58 Regardless of its source, we are confident that the redox potentials determined in this study for bCYB5A, rCYB5B and hCYB5B are valid for the stated conditions. Support for this conjecture is provided by the fact that cyclic voltammetry data for bCYB5A and rCYB5B performed in the presence of varying concentrations of divalent metal ions revealed a constant ~70 mV redox potential difference.…”
Section: Resultsmentioning
confidence: 59%
“…Type A cytochromes b 5 have been found to exhibit similar redox potentials (0 ± 10 mV; all reported potentials vs. SHE), 5861 consistent with their highly conserved amino acid sequences. Reported redox potentials for rCYB5B (−102 mV) 22 and hCYB5B (−40 mV) 28 are more negative, suggesting a need for a stronger electron delivery driving force.…”
Section: Resultsmentioning
confidence: 73%